EFFECT OF USING FACEBOOK SOCIAL NETWORK AGAINST THE IMAGING OF PT MEDIATAMA BINAKREASI - Asmulyati Azhar (SEAN Institute, 2023)
Image analysis is a picture that is in the public mind about the company. In the end perceptions will influence public attitudes, whether supporting, neutral or hostile. Company image can be formed through social media by using Facebook social media. The conclusions obtained regarding the effect of the use of Facebook social media on the image of PT Mediatama Binakreasi are good, showing the direction of positive correlation with very strong linkages. As for the assessment of the results of the hypothesis, the results show that H0 is rejected and Ha is accepted so that it can be stated that there is a significant influence between the Use of Facebook Social media on the Imaging of PT Mediatama Binakreasi.